Religions and economic development in nation building - Agunwa, Teresina V. C. (Journal of religion and human relations, 2017)
This paper starts by recognizing the importance of Religion as bedrock of moral living in building the nation as well as the major role played by Religion and Economics toward nation building. It also looks at the definition of the concept "Religion and Economics". And as well go further to stress the value of Region and Economics towards the development of any nation, and finally, suggestion on what to do in order to improve the role of Religion and Economics for the betterment of the nation. It also discuss Human being as an interacting being with others in the society which can be seen as the way in which man relate well with other fellow human being and his community in order to see the smooth running of the community or nation.